Sistem Informasi Pengenalan Perahu Pinisi Sebagai Ikon Kabupaten Bulukumba Berbasis Website - Elpi Amnur; Husni Sulaiman; Muhammad Awal Nur (Institut Teknologi dan Bisnis Bina Adinata, 2024)
This study aims to: (1) Know the information system design of Pinisi Boat Recognition as a Website-based Icon of Bulukumba Regency. (2) Knowing the appearance of the profile of the pinisi boat on the website-based Information System for Recognizing the Pinisi Boat as an Icon of Bulukumba Regency. This study uses the Waterfall method. Which consists of 6 stages, namely requirements (needs analysis), system design (system design), Coding, Testing, Implementation and Maintenance. Based on the results of this study, it can be concluded that: (1) A web-based pinisi boat recognition information system designed using the Unified Modeling Language (UML) consisting of use cases, activity diagrams, class diagrams, sequence diagrams and using the PHP programming language and MySQL as base storage the data. (2) The Pinisi Boat profile display provides information to the wider community in the form of the history of the Pinisi boat, how to make a Pinisi boat as well as 2-dimensional, 3-dimensional images and videos of the Pinisi Boat that can be seen by the wider community.